TIME EFFICIENCY OF LOADING OF FISHING SUPPLIES LIFTNET BOAT IN BUNGUS FISHING PORT WEST SUMATERA - Zain, Jonny; Rengi, Pareng; Dewi, Mutiara (Asian Journal of Aquatic Sciences, 2022)
This research was conducted from November to December 2020 using the survey method. The aim of this research is to find out what factors affect the efficiency level of loading time for lift net boats on Bungus Fishing Port. From the results of observations of 20 sample Boats that carried out fishing supplies filling activities, it showed that the amount of fuel, ice, water, the number of crew members, and the boat tonnage affected the length of time wasted which resulted in the high and low level of efficiency of filling fishing supplies at sea. The results showed that the average efficiency level of filling fishing supplies on a boat at PPS Bungus was 67,18% or less efficient. The results also showed that the greatest length of time wasted was waiting for the arrival of ice (39.68%) followed by waiting for refueling time (36.03%), drinking time (14.71%), and smoking (9.58%).